Differential transcription of expanded gene families in central carbon metabolism of Streptomyces coelicolor A3(2). Issue 6 (30th June 2020) - Schniete, Jana K.; Reumerman, Richard; Kerr, Leena; Tucker, Nicholas P.; Hunter, Iain S.; Herron, Paul R.; Hoskisson, Paul A.
Abstract : Background. Streptomycete bacteria are prolific producers of specialized metabolites, many of which have clinically relevant bioactivity. A striking feature of their genomes is the expansion of gene families that encode the same enzymatic function. Genes that undergo expansion events, either by horizontal gene transfer or duplication, can have a range of fates: genes can be lost, or they can undergo neo-functionalization or sub-functionalization. To test whether expanded gene families in Streptomyces exhibit differential expression, an RNA-Seq approach was used to examine cultures of wild-type Streptomyces coelicolor grown with either glucose or tween as the sole carbon source. Results. RNA-Seq analysis showed that two-thirds of genes within expanded gene families show transcriptional differences when strains were grown on tween compared to glucose. In addition, expression of specialized metabolite gene clusters (actinorhodin, isorenieratane, coelichelin and a cryptic NRPS) was also influenced by carbon source. Conclusions. Expression of genes encoding the same enzymatic function had transcriptional differences when grown on different carbon sources. This transcriptional divergence enables partitioning to function under different physiological conditions. These approaches can inform metabolic engineering of industrial Streptomyces strains and may help develop cultivation conditions to activate the so-called silent biosynthetic gene clusters.